The â€œGuilty Mindâ€ In The Criminal Law - Smith, Sir John (Journal of Malaysian and Comparative Law, 1997)
In 1993 a man named Penn invited a youth, Barry Kingston and a 15 year old boy to his room and there, secretly and without their consent, administered to both of them a stupefying drug. The boy was rendered insensible and, while he was in that condition, both Penn and Kingston did grossly indecent sexual things to him. Penn made a recording of what went on and took photographs. His purpose was to blackmail Kingston.